PENGARUH PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 27 MEDAN - Nurul Indah Klismei Agung; Kairuddin Kairuddin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aimed to determine the effect of the Realistic Mathematics Approach assisted by Geogebra on the mathematical problem-solving ability of eighth-grade students at SMP Negeri 27 Medan and to describe students’ answer processes in solving mathematical problems. This research used a pre-experimental method with a one group pre-test-post-test design. The population consisted of all eighth-grade students of SMP Negeri 27 Medan, with one experimental class selected through cluster random sampling. Data were collected through mathematical problem-solving ability tests. The results showed that the average pre-test score of 48.66 increased to 81.83 in the post-test. The data were normally distributed and homogeneous. Hypothesis testing showed a significance value of 0.000 < 0.05, indicating a significant effect of the Realistic Mathematics Approach assisted by Geogebra on students’ mathematical problem-solving ability. The coefficient of determination (R-Square) was 0.663, indicating a contribution of 66.3%. Students’ answer processes showed that students were able to understand problems, plan solutions, carry out solutions, and recheck the obtained results.